Cap-Mation for calvin cycle/ Fathin Farhana Mohamed Shukri ... [et al.] - Mohamed Shukri, Fathin Farhana; Ibrahim, Fadhilah; Omar, Noor Azura; Azman, Nor Suhada; Tuan Mat, Siti A’ishah (2023)
Cap-Mation is an online independent learning module that covers the whole process of the Calvin Cycle in photosynthesis. Based on feedback, most students find it difficult to comprehend and memorize the names of the molecules and reactions involved in the Calvin Cycle. Therefore, Cap-Mation was invented to aid further understanding and to promote student-centered learning. Cap-Mation is a simple hand animation using real bottle caps to represent the molecules involved. This module is also provided in a digital platform for an easily accessible learning experience for everyone, anywhere and anytime. This innovation can also be commercialized by manufacturing the bottle cap model as a teaching tool kit for Calvin Cycle.